Effects of the Highly COX-2-Selective Analgesic NSAID Etoricoxib on Human Periodontal Ligament Fibroblasts during Compressive Orthodontic Mechanical Strain. (10th March 2019) - Kirschneck, Christian; Küchler, Erika Calvano; Wolf, Michael; Spanier, Gerrit; Proff, Peter; Schröder, Agnes
Abstract : Human periodontal ligament (hPDL) fibroblasts play a major role during periodontitis and orthodontic tooth movement, mediating periodontal inflammation, osteoclastogenesis, and collagen synthesis. The highly COX-2-selective NSAID etoricoxib has a favorable systemic side effect profile and high analgesic efficacy, particularly for orthodontic pain. In this in vitro study, we investigated possible side effects of two clinically relevant etoricoxib concentrations on the expression pattern of mechanically strained hPDL fibroblasts and associated osteoclastogenesis in a model of simulated orthodontic compressive strain occurring during orthodontic tooth movement. hPDL fibroblasts were incubated for 72 h under physiological conditions with etoricoxib at 0  μ M, 3.29  μ M, and 5.49  μ M, corresponding to clinically normal and subtoxic dosages, with and without mechanical strain by compression (2 g/cm 2 ) for the final 48 h, simulating conditions during orthodontic tooth movement in compressive areas of the periodontal ligament. We then determined gene and/or protein expression of COX-2, IL-6, PG-E2, RANK-L, OPG, ALPL, VEGF-A, P4HA1, COL1A2, and FN1 via RT-qPCR, ELISA, and Western blot analyses as well as apoptosis, necrosis, cell viability, and cytotoxicity via FACS, MTT, and LDH assays. In addition, hPDL fibroblast-mediated osteoclastogenesis was assessed by TRAP staining in coculture with RAW267.4 cells for another 72 h. Gene and protein expression of all evaluated factors was significantly induced by the mechanical compressive strain applied. Etoricoxib at 3.29  μ M and 5.49  μ M significantly inhibited PG-E2 synthesis, but not COX-2 and IL-6 gene expression nor RANK-L-/OPG-mediated osteoclastogenesis or angiogenesis (VEGF-A). Extracellular matrix remodeling (COL1A2, FN1) and bone anabolism (ALPL), by contrast, were significantly stimulated particularly at 5.49  μ M. In general, no adverse etoricoxib effects on hPDL fibroblasts regarding apoptosis, necrosis, cell viability, or cytotoxicity were detected. Clinically dosed etoricoxib, that is, a highly selective COX-2 inhibition, did not have substantial effects on hPDL fibroblast-mediated periodontal inflammation, extracellular matrix remodeling, RANK-L/OPG expression, and osteoclastogenesis during simulated orthodontic compressive strain.